City of stone and silence - Wexler, Django (Wexler, Django. Wells of sorcery trilogy, 2021)
Told in two voices, while Isoka and the Soliton's crew search for a way to recapture the ship and leave the Harbor, Tori escapes the comfort of Kahnzoka's Second Ward to help run a shelter for fugitive mage-bloods and becomes embroiled in revolution.